Rattus blangorum Miller 1942 - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Rattus blangorum Miller, 1942. Proc. Acad. Nat. Sei. Phila., 94: 145. TYPE LOCALITY: Indonesia, N. Sumatra, Atjeh, Blangnanga, 3600 ft. (1097 m). DISTRIBUTION: N. Sumatra. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Rodentia (Part 5), pp. 504-560 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 548, DOI: 10.5281/zenodo.7353037